Leverage, Product Diversification, and Performance of Life Insurance Companies in Indonesia - Fanny Septina (University of Merdeka Malang, 2022)
The insurance sector is often faced with dynamic economic changes. Product adjustments to new policies and the availability of funding for the company's operational activities are crucial. This study aims to observe the effect of leverage on the financial performance of life insurance companies and examine the moderation of product diversification on the relationship of leverage to the financial performance of life insurance companies. The study also aims to confirm the pecking-order theory related leverage funding and the synergistic- effect theory about diversification product strategy. Firm-size variables and dummy periods are used as control variables. Leverage is proxied by the ratio of total debt to total equity, product diversification uses the Herfindahl index, and financial performance is proxied by return on equity. The research sample are 25 life insurance companies in Indonesia registered with the Financial Services Authority (OJK) and have published financial reports for the period of 2016 to 2020. The data analysis method uses panel regression analysis with the estimation approach of the Chow Test, the Hausman Test, the Lagrange Multiplier Test, and the moderated regression analysis. The results show that leverage has a significant negative effect on the performance of life insurance companies, and product diversification significantly strengthens the effect of leverage on the performance of life insurance companies. Firm size has a significant positive effect, while the dummy period variable has no significant effect on the performance of life insurance companies. Company with high or low leverage, both must be able to see the potential and current market risks then adjust policies. For both creditors and investor can take advantage of information to provide funding and investment on the relationship between the use of leverage and the life insurance company's product diversification strategy. Finally, the regulatory authorities of the insurance sector present as controllers of life insurance companies in serving their customers.JEL: G2, G22, M11